Machiavellian Leadership and Team-Based Organizations - Hibert, Tineke (JBE (Journal of Business and Economics); Volume 9 No.2, 2010 JBE UNKLAB, 2010)
Machiavelli and modern team-based management styles are said by several scholars to be at odds with one another.  Callahan (2004) and Buttery and Richter (2003) associate the concepts of organizational leadership power, control, and fear with traditional organizational structures and Machiavellian philosophy.  Love, collaboration, and empowerment, on the other hand, are viewed as being the exclusive domain of contemporary leadership styles.  However, it is the conclusion of this article that Machiavellian leadership and team-based organizations are not necessarily incompatible. To assume, as Callanan does, that current “collaborative work systems” are in some way superior because they do not focus on, so called, Machiavellian “tactics to increase power and hoard it as a means to ensure a leadership position” is at best naïve.  In reality, precisely the opposite is taking place:  Organizations are currently being structured into collaborative environments for the express purpose of enhancing “individual accomplishment and the building of power.” It is not the principle of maintaining and building power that has changed, but rather the manner in which this power-building is being expressed that has changed.  Powerful leadership and control should not be seen as the enemy of modern organizational structure.  Only powerful organizational leaders who are in total control of their organizations can successfully implement collaborative work systems into their organizations.